Asuhan Keperawatan Pada Tn.S Dengan Gangguan Sistem Persarafan:Stroke Non Hemoragik Di Ruang Cemapaka III RSUD Pandan Arang Boyolaluli - Sari, Ariska Dwi Etika; , Agus Sudaryanto, S.Kep., Ns., M.Kes (2015)
Background: Stroke is a brain disease because of blockage or hemorrhage with weakness symptoms, temporary paralysis or severe symptoms up to lose consciousness and death. Stroke is the third cause of death in developed countries after heart disease and cancer while in Indonesia stroke is in the first rank. Stroke patients are experiencing weakness that needs medical treatment. This disease also inflictthe highest disability in productive adult age group. Objective: To know the description of nursing care in patients with non hemorrhagic stroke that include assessment, intervention, implementation and evaluation of nursing care. Methods: The method used was case study approach. It is a scientific method to collect data, analyze the data and draw conclusions.Results: The emerging diagnosis on the case were ineffectiveness of cerebral tissue perfusion, impaired physical mobility and verbal communication barriers. After nursing care for 3x24 hours, it was obtained that no occurrence of an increase in intracranial, decrease in impaired physical mobility, and reduced verbal communication barriers. Conclusion: In doing nursing care, verbal communication problem was resolved, problem of cerebral tissue perfusion ineffectiveness and impaired physical mobility were partially resolved and thus required further treatment and cooperation among other medical team, the patient, and family was indispensable for the success of nursing care. Keywords: Stroke, nerves, non hemorrhagic, ischemia, infarction.